In Vitro Evaluation of Leakage at Implant-Abutment Connection of Three Implant Systems Having the Same Prosthetic Interface Using Rhodamine B - Antoine Berberi; Georges Tehini; Khaldoun Rifai; Farah Bou Nasser Eddine; Nabil El Zein; Bassam Badran; Haidar Akl (Hindawi Limited, 2014)
Objectives. Hollow space between implant and abutment may act as reservoir for commensal and/or pathogenic bacteria representing a potential source of tissue inflammation. Microbial colonization of the interfacial gap may ultimately lead to infection and bone resorption. Using Rhodamine B, a sensitive fluorescent tracer dye, we aim in this study to investigate leakage at implant-abutment connection of three implant systems having the same prosthetic interface. Materials and Methods. Twenty-one implants (seven Astra Tech, seven Euroteknika, and seven Dentium) with the same prosthetic interface were connected to their original abutments, according to the manufacturers' recommendation. After determination of the inner volume of each implant systems, the kinetic quantification of leakage was evaluated for each group using Rhodamine B (10−2 M). For each group, spectrophotometric analysis was performed to detect leakage with a fluorescence spectrophotometer at 1 h (T0) and 48 h (T1) of incubation time at room temperature. Results. Astra Tech had the highest inner volume (6.8 μL), compared to Dentium (4 μL) and Euroteknika (2.9 μL). At T0 and T1, respectively, the leakage volume and percentage of each system were as follows: Astra Tech 0.043 μL or 1.48% (SD 0.0022), 0.08 μL or 5.56% (SD 0.0074), Euroteknika 0.09 μL or 6.93% (SD 0.0913), 0.21 μL or 20.55% (SD 0.0035), and Dentium 0.07 μL or 4.6% (SD 0.0029), 0.12 μL or 10.47% (SD 0.0072). Conclusion. The tested internal conical implant-abutment connections appear to be unable to prevent leakage. In average, Astra Tech implants showed the highest inner volume and the least leakage.